Kecemasan Menghadapi Tes (Test Anxiety) Dan Dampaknya Terhadap Aktivitas Belajar - Revilla, Lina (IAIN Samarinda, 2009)
In education process, the objective of test given to the students is to find out the change of attitude and also new skill that achieve by the students after teaching and learning process. Many times, test in students’ mind is a problem that cause test anxiety. The anxiety theory differentiates between cognitive component which is known as worry component and emotional component or affective component, as two components of test anxiety. Cognitive component or worry component administers mind that comes with anxiety such as test failure, and the consequence of the test failure is potential to cause the anger of parents, drop out, and also embarrassed feeling. Whereas the emotional component or affective component describes the physiological reaction and emotion that appear when students face the test. It’s important to note that most of people feel the anxiety when they have to prove their productivity. Test anxiety that encountered by people will be influenced by their ability to finish the test. Some researches prove that test anxiety can influence academic productivity, self-esteem, related to students’ self-defense and the fear of negative valuation. Hence, to anticipate the negative effect that caused by test anxiety, it is important to held anxiety management and learning skill.